2015
DOI: 10.1007/s10554-015-0717-8
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic result of index PCI determines the presence of right ventricular infarction in patients with acute inferior myocardial infarction

Abstract: It is still a matter of debate which patients with acute inferior myocardial infarction are at increased risk of developing right ventricular (RV) myocardial infarction (RVMI). Cardiac magnetic resonance imaging (CMRI) with late enchancement (LE) is regarded as the gold standard for RVMI assessment. We aimed to determine the impact of initial angiographic status and salutary effect of primary percutaneous coronary intervention (PCI) on the presence of RVMI. In 114 patients undergoing emergency angiography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
1
0
2
Order By: Relevance
“…Согласно результатам КАГ при инфаркте ПЖ, сопровождающего нижний ОИМ ЛЖ, единственной ИСА остается ПКА, в отличие от изолированного нижнего ОИМ, когда ИСА выступают как ПКА, так и ОА. В нашей работе, как и у других исследователей, основной причиной инфаркта ПЖ оказалась окклюзия проксимальной части ПКА [2,3,5,11]. Помимо проксимальной и медиальной окклюзии ПКА у 11 (18,7%) пациентов с инфарктом ПЖ наблюдали окклюзию ПКА на дистальном уровне.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Согласно результатам КАГ при инфаркте ПЖ, сопровождающего нижний ОИМ ЛЖ, единственной ИСА остается ПКА, в отличие от изолированного нижнего ОИМ, когда ИСА выступают как ПКА, так и ОА. В нашей работе, как и у других исследователей, основной причиной инфаркта ПЖ оказалась окклюзия проксимальной части ПКА [2,3,5,11]. Помимо проксимальной и медиальной окклюзии ПКА у 11 (18,7%) пациентов с инфарктом ПЖ наблюдали окклюзию ПКА на дистальном уровне.…”
Section: Discussionunclassified
“…По электрокардиограмме (ЭКГ) у каждого второго (52,7%) обследованного с нижним инфарктом выявляют инфаркт ПЖ [4]. Нарушение коронарного кровотока по шкале TIMI (Thrombolysis In Myocardial Infarction) < 3 как минимум в одной ветви ПЖ (отношение шансов 4,07; 95% доверительный интервал 1,24-13,33; р = 0,02) было независимым ангиографическим предиктором подъема сегмента ST ≥ 1 мм в V 4 R [5]. Подъем сегмента ST в дополнительных правых грудных отведениях V 3 R-V 4 R, отражающий поражение ПЖ, признан предиктором неблагоприятного исхода, высокого риска артериальной гипотензии в остром периоде инфаркта миокарда, риска аритмии и гемодинамически значимой синусовой брадикардии.…”
Section: о р и г и н а л ь н а я с т а т ь яunclassified
“…Such echocardiographic changes are a strong foundation for emerging complications and hemodynamic impairment that leads to RV dysfunction responsible for significantly increased morbidity and mortality in patients with RVMI [6,[17][18][19]. In addition, angiographic studies revealed that the right coronary artery (RCA) was the most often the infarct-related artery (IRA), especially, its proximal part [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%